(untitled) (Journal of Computational Mathematics, 1985)
Starting from the canonical boundary reduction, this paper studies an approximate differential boundary condition and an approximate integral boundary condition on an artificial boundary for the exterior problem of a harmonic equation, and gives an error estimate for the latter. This estimate reveals the relationship between the error and the approximate grade boundary conditions as well as the radius of the artificial boundary.